A 16-year-old with ST elevation myocardial infarction: case report and review of the literature. (2nd October 2015) - Hill, Dustin; Waldman, Adam; Vivek, Deepak
Abstract: Chest pain in young adults presents a unique diagnostic challenge, placing young patients at an increased risk to be misdiagnosed, as this patient population typically does not demonstrate the traditional risk factors associated with cardiovascular disease. This study details the case of a 16-year-old male who presented with new-onset chest pain and ST elevation on electrocardiogram. His history was unremarkable for known cardiac risk factors, but laboratory evaluation demonstrated markedly elevated troponins and electrocardiographic findings confirmed ST-segment elevation myocardial infarction. Coronary angiography demonstrated 100% occlusion of the left anterior descending artery, which was managed with percutaneous transluminal coronary angioplasty, thrombectomy, and bare-metal stenting. The patient had an uneventful recovery. This study examines the major causes of ST elevation myocardial infarction in young adults and reviews the major differences between younger and older myocardial infarction populations with emphasis on risk factor profile, pathophysiological mechanisms, clinical presentation, angiographic findings, and prognosis. This review highlights the need for consideration of a wide differential in younger subsets of the population presenting with chest pain and ST elevation. The implementation of current adult management protocols and guidelines for ST elevation myocardial infarction should not be overlooked due to age. Given the potential for premature death and long-term disability with resulting individual and societal consequences, it is crucial to understand the importance of correct diagnostic evaluation in this clinical scenario.